Optical phase aberration correction with an ultracold quantum gas - Hill, Paul; Lunt, Philipp; Reiter, Johannes; Galka, Maciej; Preiss, Philipp; Jochim, Selim (Physical review, 2024)
We present an optical aberration correction technique for ultracold quantum gas experiments which directly utilizes the quantum gas as a wave-front sensor. The direct use of the quantum gas enables correcting aberrations that are otherwise impractical to measure, e.g., introduced by vacuum windows. We report a root-mean-square precision and accuracy of 0.01⁢𝜆 and 0.03⁢𝜆, respectively, and also show independently the reduction of aberrations through measurement of the trap frequency of our optical tweezer. These improvements were achieved for a tweezer size that is well below our imaging resolution. The present work is in particular intended to serve as a tutorial for experimentalists interested in implementing similar methods in their experiment.